Building a proper administrative procedure for the use of mediation in public law disputes (conceptual basis) - Tokarieva, Kseniia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article is devoted to the study of the conceptual basis of building a proper administrative procedure for the use of mediation in public law disputes. In the context of constant reform of the justice system in order to improve the mechanisms of access of citizens to instruments of protection of rights, the introduction of mediation - an alternative way of resolving disputes - remains relevant. The introduction of mediation in public law disputes requires a balanced systemic approach that will cover all important aspects of the procedure and facilitate its proper functioning. It is determined that the application of mediation to public law disputes due to their special nature requires legal regulation. The main conceptual provisions for the construction of a proper administrative procedure for the use of mediation in public law disputes have been formed: 1) minimal state and legal influence; 2) harmonious addition of the procedure of administrative appeal and judicial proceedings by mediation, and not their exclusion of each other; 3) ensuring the variability of mediation models in order to effectively maximize its potential; 4) professionalism of the mediator as a conceptual guideline of mediation, determined by the nature of public law disputes; 5) improvement of the legal status of the subjects of power (supplementation and expansion of their powers in terms of initiative and participation in mediation); 6) creation of an effective mechanism for the implementation of agreements based on the results of mediation as a guarantee of security to increase public confidence in the new administrative procedure for the use of mediation.